Hospital cost of pediatric patients with complicated acute sinusitis. (January 2016) - Padia, Reema; Thomas, Andrew; Alt, Jeremiah; Gale, Craig; Meier, Jeremy D.
Abstract: Objective: Review costs for pediatric patients with complicated acute sinusitis. Methods: A retrospective case series of patients in a pediatric hospital was created to determine hospital costs using a standardized activity-based accounting system for inpatient treatment between November 2010 and December 2014. Children less than 18 years of age who were admitted for complicated acute sinusitis were included in the study. Demographics, length of stay, type of complication and cost of care were determined for these patients. Results: The study included 64 patients with a mean age of 10 years. Orbital cellulitis (orbital/preseptal/postseptal cellulitis) accounted for 32.8% of patients, intracranial complications (epidural/subdural abscess, cavernous sinus thrombosis) for 29.7%, orbital abscesses (subperiosteal/intraorbital abscesses) for 25.0%, potts puffy tumor for 7.8%, and other (including facial abscess and dacryocystitis) for 4.7%. The average length of stay was 5.7 days. The mean cost per patient was $20, 748. Inpatient floor costs (31%) and operating room costs (18%) were the two greatest expenditures. The major drivers in variation of cost between types of complications included pediatric intensive care unit stays and pharmacy costs. Conclusion: Although complicated acute sinusitis in the pediatric population is rare, this study demonstrates a significant financial impact on the health care system. Identifying ways to reduce unnecessary costs for these visits would improve the value of care for these patients.